2014
DOI: 10.1088/0004-637x/784/1/17
|View full text |Cite
|
Sign up to set email alerts
|

TIME-RESOLVED ANALYSIS OFFERMIGAMMA-RAY BURSTS WITH FAST- AND SLOW-COOLED SYNCHROTRON PHOTON MODELS

Abstract: Time-resolved spectroscopy is performed on eight bright, long gamma-ray bursts (GRBs) dominated by single emission pulses that were observed with the Fermi Gamma-ray Space Telescope. Fitting the prompt radiation of GRBs by empirical spectral forms such as the Band function leads to ambiguous conclusions about the physical model for the prompt radiation. Moreover, the Band function is often inadequate to fit the data. The GRB spectrum is therefore modeled with two emission components consisting of optically thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 64 publications
11
104
1
Order By: Relevance
“…The choice of spectral model also plays an crucial role in determining the slope and normalization of GCs. The results of Burgess et al (2014); Iyyani et al (2015) where a physical synchrotron model was used to fit the spectra of the same GRBs used in this study produced GCs with different slopes than what is found here with empirical spectral models. This is due to the different curvature of these models around the νFν peak which results in different E peak 's from the spectral fits.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The choice of spectral model also plays an crucial role in determining the slope and normalization of GCs. The results of Burgess et al (2014); Iyyani et al (2015) where a physical synchrotron model was used to fit the spectra of the same GRBs used in this study produced GCs with different slopes than what is found here with empirical spectral models. This is due to the different curvature of these models around the νFν peak which results in different E peak 's from the spectral fits.…”
Section: Discussionmentioning
confidence: 71%
“…It has been claimed that the use of multi-component spectra tighten the observed GC in some GRBs (Guiriec et al 2015). I therefore use the time-resolved luminosity and E peak from Band function (Band et al 1993) fits of the sample of GRBs analyzed in Burgess et al (2014). These GRBs are single pulsed in their lightcurves and were analyzed with physical synchrotron models as well as the empirical Band function.…”
Section: Application To Real Grbsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed emission can be entirely from the photosphere wherein the broadness is contributed by the continuous or localised subphotospheric dissipation of the kinetic energy or Poynting flux (Beloborodov 2010(Beloborodov , 2013Giannios 2012;Pe'er, Mészáros & Rees 2005;Iyyani et al 2015), or may be due to the geometrical effects of the jet emission and its structure (Lundman, Pe'er & Ryde 2013;Beloborodov 2011;Basak & Rao 2015a). Or, the photospheric emission can be a sub-dominant component (Burgess et al 2014;Axelsson et al 2012;Iyyani et al 2013;Guiriec et al 2011Guiriec et al , 2013. All the models have certain pros and cons and confront issues in justifying the constraints obtained from observations.…”
Section: Introductionmentioning
confidence: 99%